Measuring factors of employees' job satisfaction among lecturers in UiTM Melaka / Nor 'Aqilah Ahamad Baharudin - Ahamad Baharudin, Nor 'Aqilah (Faculty of Communication and Media Studies, 2018)
This research is basically aimed to recognize and measure the factors of employees' job satisfaction among lecturers specifically in the organization of UiTM Melaka , Campus of Alor Gajah. In the world of development, this topic is prominent in its way as every organizations need to improve their employees' satisfaction to produced a decent job (Wan Ahmad & Abdurahman, 2015). There were many familiar present studies in this field that may be a strong stand to be referred. By using Maslow's Hierarchy of Needs Theory and Herzberg Motivator-Hygiene Theory which are related to job satisfaction field , there were four relevant factors of employees' job satisfaction; work relationships, job security, self efficiency and payment and reward. A survey is conducted based on Krejcie and Morgan Table , N=340, S=181 . A total of 212 questionnaires were answered by the lecturers of UiTM Melaka , Campus of Alor Gajah as purposely sampling and produced the results. The findings of this research resulted Multiple Linear Regress ion Method that there were positive significant on three of the factors; work relationship , self-efficiency, payment and reward , while negative significant to the factor job security. To promote the satisfaction of the staffs , the organization must consider this variable in order to gain the best brain (Mustapha & Zakaria, 2013) .